Da'wah Versus Patriarchy Messages: Semiotical Analysis of Lyrics "Nanti Kita Seperti Ini" - Avicena Ismail NoorEsa; Burhanudin Al Ghoni; Izza Muhammad Abdilah; Salsabila Qotrunnada; Kholifatul Fauziah; Ikhwan Ansori (Proceedings International Conference on Sustainable Innovation (ICoSI), 2023)
Da'wah is an invitation to people (mad'u) to believe and obey what Allah and His Messenger command. In the Qur'an, there are three methods of da'wah, namely wisdom, good example, and arguing in a good way. In its implementation, songs can be one of the means of da'wah. Songwriters can include da'wah messages in their song lyrics. The author finds indications of da'wah messages, one of which is in the lyrics of a viral song on social media entitled "Later we will be like this". The purpose of this study is to find a da'wah message in the lyrics of the song. This research is an analysis of da'wah messages using a qualitative approach to the type of library research. The data collection technique used in this research is to use documentation techniques. In analyzing the lyrics of this song, the author uses the semiotic analysis theory of Charles Sanders Peirce model. The results of the analysis method, the author found a contradiction in the song lyrics between da'wah messages and patriarchal messages. There are three categories of da'wah messages contained in the lyrics of this song, namely aqidah, Syariah, and akhlaq.